2018
DOI: 10.3390/jof4030087
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in the Management of Onychomycosis

Abstract: Onychomycosis is an increasingly common fungal nail infection, chiefly caused by dermatophyte fungi. The disease is notoriously difficult to treat due to the deep-seated nature of fungi within the nail plate, prolonged treatment requirements, poor patient adherence and frequent recurrences. Given the poor efficacy of currently available topical and systemic therapies, there is a renewed interest in exploring alternative treatment modalities for onychomycosis. Natural therapies, physical treatments and various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 57 publications
0
34
0
1
Order By: Relevance
“…A 2013 systemic review of 11 population-based and 21 hospital-based studies showed that the mean prevalence of onychomycosis in North America and Europe was 4.3% (95% confidence interval: 1.9 to 6.8) in the population-based studies and 8.9% (95% confidence interval: 4.3 to 13.6) in the hospital-based studies [ 38 ]. There is evidence that the prevalence is rising, possibly because of longer life expectancy, use of occlusive modern footwear, increased prevalence of obesity, and increased urbanisation [ 17 , 39 , 40 ]. The condition is much more common in adults than in children and the prevalence increases with age [ 8 , 14 , 36 , 41 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…A 2013 systemic review of 11 population-based and 21 hospital-based studies showed that the mean prevalence of onychomycosis in North America and Europe was 4.3% (95% confidence interval: 1.9 to 6.8) in the population-based studies and 8.9% (95% confidence interval: 4.3 to 13.6) in the hospital-based studies [ 38 ]. There is evidence that the prevalence is rising, possibly because of longer life expectancy, use of occlusive modern footwear, increased prevalence of obesity, and increased urbanisation [ 17 , 39 , 40 ]. The condition is much more common in adults than in children and the prevalence increases with age [ 8 , 14 , 36 , 41 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…The infection can have a significant impact on patient quality of life, causing pain, discomfort and physical impairment [3]. If left untreated, the infection can spread to other nails as well as to other parts of the body [4]. The organisms most commonly associated with onychomycosis include dermatophytes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…amorolfine and ciclopirox) and combination therapy with systemic and topical antifungals [6,7]. The choice of therapy depends on the extent and severity of infection, the pathogen responsible, risk of drug interactions or adverse events and success or failure of previous treatment [4]. Systemic therapy is used widely because of its easy accessibility, low cost and high efficacy, but it may be associated with systemic adverse events (AEs) and drug interactions and require laboratory monitoring [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oral treatment is the most effective, but long-term (at least 6 months) drug administration may lead to severe adverse reactions, interactions with other medicines and is not acceptable during lactation or pregnancy [ 2 ]. Local treatment of onychomycosis lasts over a year, with the efficacy of up to 50%, but interactions with other medicinal products are avoided, and treatment can be given to all patient groups [ 3 ]. However, local infection treatment is complicated by the structure of the nail, made up of 80% keratin.…”
Section: Introductionmentioning
confidence: 99%